Application of Legowo Range to The Growth and Result of Three Sorgum Varieties (Sorghum bicolor L. Moench) - Silvia Fauziatuz Zuhro; Rahmad Jumadi; Suhaili (Universitas Muhammadiyah Sidoarjo, 2022)
Sorghum (Sorghum bicolor L. Moench) is a type of cereal plant that has considerable potential to be developed in Indonesia. Sorghum seeds contain 73% carbohydrates, 3.5% fat, and 10% protein depending on the variety and planted area. Sorghum is resistant to drought and relatively resistant to pests and diseases. This research was conducted with the aim of knowing the interaction between the jajar legowo planting system and three varieties of sorghum. This research was conducted at the Seed Center of the Agriculture Service, Kebomas District, Gresik Regency. The main ingredients of this experiment were sorghum seeds of the Numbu variety obtained from the Faculty of Agriculture, University of Muhammadiyah Gresik, the Bioguma 3 Agritan variety and the KD-4 variety obtained from the Tripe Agricultural Extension Center and Phonska NPK fertilizer. This study used a factorial randomized block design (RAKF) with two factors, namely jajar legowo and varieties. The two factors were combined to obtain 9 treatments. The observed variables consisted of germination rate, plant height, stem diameter, number of leaves, flowering age, harvest age, panicle length, wet weight of planted seeds, dry weight of planted seeds and estimated dry weight of seeds per hectare. The treatment that showed a significant effect was then tested further with Duncan's multiple range test at the 5% test level. The results showed that there was no significant interaction between the jajar legowo planting system and varieties on the variables of plant growth and yield.